SD-WAN: how the control of the network can be shifted from core to edge - Troia, Sebastian; Moreira Zorello, Ligia Maria; Maier, Guido (2021 International Conference on Optical Network Design and Modeling (ONDM), 2021)
Wide Area Network (WAN) reliability has become an imperative for enterprises with Cloud-hosted applications and distributed branch offices. Many solutions and different network technologies have been proposed over the years, such as leased lines, frame relay, or Multi-Protocol Label Switching (MPLS). Those solutions offer Quality of Service (QoS) at costs that are too high for companies today. Software-Defined Wide Area Network (SD-WAN) is regarded as the promising technological solution for the next generation of enterprise networks, since it is capable of increasing network reliability and agility while reducing costs. In this paper, we provide an overview of this technology, addressing its advantages and research opportunities.